Analisis Potensi Penghematan Penggunaan Air PDAM Untuk Kebutuhan Air Domestik Pegawai Di Lingkungan UP. PERAK Grati - Ammar Asof; Rochmad Romadon (JURNAL POWERPLANT, 2015)
PLTGU Grati is one of the central power plants, shadow by PT INDONESIA POWER in East Java. One of the main need to support existing power plant operations is water availability that is quite good quality based on the design of the equipment. To fulfill the needs water in PLTGU Grati then built center (desalination water purification plant).. In addition to used to operational needs power plants, water desalination products also used for the fire fighting and sufficient water needs domestic workers in environmental PLTGU Grati. Water Needs that was big enough domestic this can be replaced by using water fee is cheaper pdam. This becomes the background of the project end entitled Analysis potential energy saving water use PDAM TO water needs domestic workers in ENVIRONMENTAL PLTGU GRATI.research projects end is done by observing the surgery was happening in desalination technologies, namely the evaporation and condensation. By knowing operation process desalination we can know that the operation desalination requires a great deal to electricity usage, steam and chemical materials. Based on the result calculation that has been done, so it can be known what was needed for production water desalination is 84612 / m3 far more expensive than water tariff pdam Rp 17357 / m3. The use of water Based on data flowmeter domestic we can know price water use domestic servants 163 m3/day. Based on data that we can know the potential energy saving that we can get income of Rp 333,578,074 per month. And to support this project is required to pump motor of 3.75 HP.